REVIEW: G. Corbetta e P. Morosetti, Le vie della crescita. Corporate strategy e diversificazione del business, Egea, Milano, 2018. - Palazzi, Federica (Piccola Impresa / Small Business, 2020)
The book analyzes the ways of growth that can be undertaken by multibusiness-type companies, highlighting the advantages and disadvantages of the multiple alternatives, the resources, and capabilities necessary to support these paths, as well as the numerous pitfalls not to be underestimated. For this reason, the volume represents a useful tool, a reference benchmark, also for micro and small business entrepreneurs interested in starting development paths, often unavoidable in the current globalized context of the digital economy, to increase the chances of long-term survival.